Stress management and coping strategies of barangay health workers in Binangonan, Rizal - Daileg, Ervin Justin S.; Roxas, Tonie Rose C.; Yoto, Wilma J.; Ines, Billy M. (2025)
This study was primarily aimed at determining the Stress Management and Coping Strategies of Barangay Health Workers in Binangonan, Rizal. The researchers utilized a descriptive method of research to determine the perception of barangay health workers in Binangonan, Rizal in terms of causes of stress, primary cognitive appraisal, secondary cognitive appraisal, problem Focused coping and emotion-focused coping. The respondents were 148 barangay health workers in Binangonan, Rizal. The researchers made use of a partially adapted questionnaire checklist. The first part was about the profile of barangay health workers in Binangonan, Rizal. The second part was all about the causes of stress experienced by BHWs. The third was about the respondents' perception in primary and secondary cognitive appraisal. The last one was about the perception of the respondents in problem-focused coping and emotion-focused coping strategies. The data gathered tabulated and subjected to descriptive and statistical analysis using frequency, percentage and rank distribution, weighted mean, and one-way analysis of variance for the interpretation of gathered data. Based on the data gathered and appropriate statistical analysis, the majority of respondents 37.1% aged 55 and above, 88.1% were female, 54.5% married, 70.6% volunteers, 49.7% high school graduates, and 30.8% have served as barangay health workers in Binangonan, Rizal for over eight years. As to perception of respondents on causes of stress experienced by Barangay Health Workers, it was revealed that "limited financial resources" ranked first with 47 out of 143 or 32.9 percent of respondents. As to the respondents' perception of Primary Cognitive Appraisal, item "Effectively managing desired activities despite work schedule" ranked first with a mean of 3.47 and has the verbal interpretation as "Often". While in terms of Secondary cognitive Appraisal, item "Participating in seasonal social events (e.g., Christmas parties, year-end parties) funded by the barangay for relaxation." ranked first with a mean of 3.99 and has "Often" as verbal interpretation. Lastly, in regards to the perception of the respondents with respect to Problem-Focused Coping Strategies, it revealed that "Managing time efficiently." ranked first with a mean of 3.60 and was interpreted as "Often". While in terms of Emotion-focused Coping, "Listening to music or watching favorite movies or television shows to relax." ranked first with a mean of 3.89 and was interpreted as "Often". In relation to the significant differences in the respondents' perceptions of stress management practices and coping strategies based on their demographic profile, age was found to have significant difference in problem-focused coping, with a p-value of 0.024. Similarly, employment status showed statistically significant difference in both primary cognitive appraisal and problem-focused coping, with p-values of 0.030 and 0.044, respectively. Furthermore, the number of years of service as a Barangay Health Worker demonstrated significant differences in secondary cognitive appraisal, problem-focused coping, and emotion-focused coping, with p-values of 0.006, 0.000, and 0.000, respectively. Based on the summary of findings, the researchers concluded that the respondents are still able to effectively manage their desired activities despite their work schedules, indicating a positive primary cognitive appraisal. To cope with stress, they often participate in seasonal social events such as Christmas parties and year-end gatherings funded by the barangay, which serve as a form of secondary cognitive appraisal for relaxation. Among the various stress-coping strategies, participation in sports activities conducted in the community is the least utilized. Most respondents tend to use emotion-focused coping strategies rather than problem-focused ones, preferring positive reframing over taking direct action. Those aged 55 and above particularly favor emotion-focused coping strategies. Female respondents, who make up the majority, experience higher levels of stress compared to their male counterparts. This is attributed to the multiple responsibilities they manage both in the workplace and at home. Furthermore, the respondents demonstrate empowerment through increased knowledge of family planning and other health-related areas. The primary cause of stress among Barangay Health Workers is identified as limited financial resources. From the findings of the study, the researchers recommended to enhance financial support to mitigate burnout, and local government units along with partnering health agencies should prioritize providing regular stipends, allowances, or performance-based incentives. Coping interventions should be age-sensitive, incorporating accessible physical activities, peer support groups, and cognitive-behavioral strategies that build emotional resilience. It is also essential to support and recognize volunteers through non-monetary forms of appreciation such as healthcare privileges, skill development opportunities, and formal commendations, which can significantly boost morale and retention. Promoting physical wellness activities should be an integral part of community health programs, with a strong emphasis on regular exercise, proper nutrition, and mental health support. Additionally, support and training programs must be customized based on demographic factors to ensure that each BHW receives
Undergraduate Thesis
Includes bibliographical references